Acil cerrahi ünitesined akut apandisit tanısıyla izlenen hastaların anksiyete düzeylerinin belirlenmesi - Bekler, Saime (My University, 2004)
Bu çalışma, acil cerrahi ünitesinde akut apandisit tanısıyla izlenen hastaların anksiyete düzeylerini belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Araştırmanın evrenini, İstanbul il sınırları içerisinde bulunan SSK Okmeydanı Eğitim Hastanesi acil cerrahi ünitesine 1 Ocak 2002-31 Aralık 2002 tarihleri arasında başvurmuş, akut apandisit ön tanısı alarak gözlemde tutulmuş hastalar oluşturmuştur. Örnekleme 304 hasta alınmıştır. Veriler literatür bilgisi ve uzman görüşü dikkate alınarak hazırlanan veri toplama formu ve durumluk-kaygı ölçeği aracılığı ile toplanmıştır. İstatistiksel olarak sayı, yüzdelik ve t testi ile değerlendirilmiştir. Araştırma sonucunda; eğitim düzeyleri farklı, tüm yaş grubundaki erkek ve kadın hastaların %6.6'sının hafif düzeyde anksiyete, %55.3'ünün orta düzeyde anksiyete, %38.2'sinin ise ağır düzeyde anksiyete yaşadığı belirlenmiştir. Sağlık olanaklarından yararlanma durumları, geçmiş hastane deneyimleri, acil cerrahi ünitesine başvurma süreleri, acil cerrahi ünitesinde bulunma nedeni hakkında bilgi edinme kaynaklarının hastalarda orta düzeyde anksiyete yaşanmasına neden olduğu belirlenmiştir. Acil cerrahi ünitesinde akut apandisit tanısıyla izlenen hastaların %55.3'ünün gürültü, %24.0'ının aydınlatma sistemi, %24.0'ının yatağın kirli veya bozuk olması, %36.5'inin sedye üstünde yatma, %39.1'inin gereksinimlerin istenildiği şekilde karşılanamaması, %74.0'ının cerrahi girişimin varlığı/ olasılığı, %26.0'ının tanı konulamama, %36.5'inin sağlık personelinin tutumu, %26.6'sının tıbbi kelimelerin sık kullanılması, %22.4'ünün zaman kaybı ve %22.0'ının mahremiyete özen gösterilmeme gibi nedenlerden olumsuz etkilendileri ve orta düzeyde anksiyete yaşadıkları belirlenmiştir Sonuç olarak ; acil cerrahi ünitesinde akut apandisit tanısıyla izlenen hastaların sosyodemografik özelliklerinin ve hastalık bulgularının farklı olduğu, acil cerrahi ünitesinde izlenme süreleri boyunca olumsuz etkilendikleri faktörlerin bulunduğu ve hastaların tümünün farklı düzeylerde anksiyete yaşadıkları belirlenmiştir. Bu sonuçlar, acil cerrahi ünitesinde akut apandisit tanısıyla izlenen hastaların anksiyete düzeylerinin azaltılmasında acil bakım ekibine ve ekibin temel taşını oluşturan acil bakım hemşiresine önemli roller düştüğü gerektiğini göstermektedir. DETERMINING OF THE ANXIETY LEVELS OF THE PATIENTS THAT ARE FOLLOWED WITH DIAGNOSIS OF ACUTE APPENDICITIS IN THE EMERGENCY SURGERY UNIT

This study has been conducted within a spirit of characterization in order to determine the anxiety levels of the patients that were followed with diagnosis of acute appendicitis in the emergency surgery unit. The study has been based on the patients who have applied to the Emergency Surgery Unit of SSK Okmeydanı Eğitim Hastanesi (Organization of Social Security, Okmeydanı Education Hospital), which is within the borders of Istanbul, between dates: 1 January 2002 and 31 December 2002 and who have been pre-diagnosed with acute appendicitis. 304 patients were included in the sampling. The related data has been collected by means of data collection form and situational - anxiety scale which has been prepared by taking into consideration the literature knowledge and views of specialists. It has been statistically evaluated by numbers, percentages and t test. The results of the study have shown that among the patients, who had different levels of education, who belonged to all age groups and who consisted of both males and females, 6.6% had lower levels of anxiety while 55.3% had medium and 38.2% had extreme levels of anxiety. It has also been determined that the patients' possibility to utilize health services, their past hospital experiences, their application times to the emergency surgery units and their way of obtaining information on the cause for their being in the said units have caused them to experience medium levels of anxiety. The patients who were followed in the emergency surgery unit with diagnosis of acute appendicitis have expressed that they were negatively affected and experienced medium level of anxiety due to the following reasons with their respective percentages included: 55.3% from noise, 24.0% from illumination system, again 24.0% from dirty or untidy beds, 36.5% from lying on stretcher, 39.1% from the insufficient meeting of their requirements, 74.0% from the presence / probability of surgical attempts, 26.0% from of non-diagnosis, 36.5% from the attitudes of the health personnel, 26.6% from the frequent utilization of medical terms, 22.4% from loss of time and 22.0% form disrespect for privacy. Conclusion: It has been determined that the socio-demographical particularities and disease findings of the patients that were followed with diagnosis of acute appendicitis in the emergency surgery unit were different and also that they were negatively effected from particular factors during their supervision in the emergency surgery unit and that all of them suffered from anxiety. These results show that the emergency team and the emergency care nurse, who is the core stone of the team, bear great responsibilities in the lessening of the anxiety levels of the patients that are followed with diagnosis of acute appendicitis in the emergency surgery unit.
Keywords: Hemşireler